Analysis of Fitness Level Tall Sd Country Physical Student Class The Magnificent Acehnese - Mansur, Mansur; Syukriadi, Amanda; Razali, Razali; Fajrial, Jul; Ambiya, Fachrizal; Razaq, Rahmatul (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. Physical fitness is incorrect. One important aspect for every individual, including students, is to maintain a good level of fitness. With optimal physical condition, all activities can be performed efficiently without experiencing fatigue. The fitness levels of elementary school students can positively correlate with their academic and non-academic performance, contributing to their overall health and development. Materials and Methods. Examine This targeting For physical fitness knowledge level, high school students in Kajhu, Aceh Besar. The methodology employed a quantitative approach with a specific type of study. This is descriptive. Demographic analysis A total of 128 participants were involved in the educational sample, resulting in a comprehensive research study with 128 participants. Methodology for gathering data in the study This involves the application of TKJI to all students in Grade IV and V at Public Elementary School Kajhu. The data collection involved administering the TKJI test, which comprised a 40-meter run, hanging elbow bend, lying down, sitting for 30 seconds, upright jump, and a 600-meter run. Data analysis techniques were applied using average formulas and percentages. Results. The analysis of results data indicates the fitness levels of high school students in the class. The Great Acehnese is as follows: The physical fitness level of the student is recorded at 13.36, which falls into the lower category. The details are as follows: (1) A total of 4 individuals, representing 6.67%, fall into the Good once category. (2) There are 14 individuals, accounting for 23.33%, in the good category. (3) One individual, or 1.67%, is classified in the moderate category. (4) A group of 28 individuals, making up 46.67%, is categorised as less. (5) Lastly, 13 individuals, or 21.67%, are identified in the not enough very category. Conclusion . The average fitness level of the physical education student is 10.51, categorised as below standard, with the following details: Negative response. There is a student, the princess, who achieved a category of Good or Good once, with a total of 1 person. 1.47% fall within the moderate category, while 41 individuals, representing 60.29%, are classified in the less category. Additionally, there are 26 individuals noted. 38.24% fall into the category of insufficiently represented.